2013
DOI: 10.1068/p7487
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Central and Peripheral Vision in Expert Decision Making

Abstract: Abstract. The purpose of this study was to investigate the role of central and peripheral vision in expert decision making. A gaze-contingent display was used to selectively present information to the central and peripheral areas of the visual field while participants performed a decision-making task. Eleven skilled and eleven less-skilled male basketball players watched video clips of basketball scenarios in three different viewing conditions: full-image control, moving window (central vision only), and movin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 41 publications
5
92
0
Order By: Relevance
“…However, the eye-tracker employed in this study was unable to account for potential information pick-up from peripheral vision, and so future research should use more suitable technology to better elucidate the role of central and peripheral vision in sports officiating (e.g., gaze-contingent displays). Indeed, research among sport performers has shown that more highly skilled performers tend to make better use of both central and peripheral vision when making decisions (e.g., Ryu, Abernethy, Mann, Poolton, & Gorman, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, the eye-tracker employed in this study was unable to account for potential information pick-up from peripheral vision, and so future research should use more suitable technology to better elucidate the role of central and peripheral vision in sports officiating (e.g., gaze-contingent displays). Indeed, research among sport performers has shown that more highly skilled performers tend to make better use of both central and peripheral vision when making decisions (e.g., Ryu, Abernethy, Mann, Poolton, & Gorman, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a series of recent experiments, we have shown that skilled athletes are better able to make use of their peripheral vision when performing a domain-specific task (Ryu, Abernethy, Mann, & Poolton, 2015;Ryu, Abernethy, Mann, Poolton, & Gorman, 2013). In those studies, the decision-making ability of skilled and lessskilled basketball players was tested when viewing video footage of basketball game scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these results might indicate that other cognitive process must be involved in the performance of players regarding their visual behaviour, such as peripheral vision and the attention process 7,29 . Alternatively, it also has implications for the assessment or training of soccer players' decision-making or tactical knowledge based on video tests.…”
Section: Discussionmentioning
confidence: 99%